Frequency of Secondary Hemorrhage Post Tonsillectomy by Dissection and Ligation Method Using Silk 2.0 for Hemostasis: Secondary Hemorrhage Post-Tonsillectomy by Dissection and Ligation Method Using Silk 2.0 - Ali, Noman; Hussain, Shahid; Akram, Absar; Rehman, Abdul; Faheem, Abdul Jabbar; Rafiq, Shumaila (Pakistan Journal of Health Sciences, 2026)
Hemorrhage is one of the most common and serious complications in post-tonsillectomy follow-up. Objective: To find the frequency of post-tonsillectomy hemorrhage using silk 2.0 for hemostasis. Methods: A cross-sectional analytical study was conducted at the Department of Otorhinolaryngology, District Headquarter Teaching Hospital, Gujranwala, from April 2025 to December 2025. 109 patients aged 5–14 years diagnosed with chronic tonsillitis underwent bilateral tonsillectomy by Dissection and Ligation with 35-40 minutes of Surgery duration under general anesthesia. Hemostasis was achieved exclusively using Silk 2.0 suture ligation. Patients were monitored for 28 days postoperatively for evidence of secondary hemorrhage. Data were analyzed using SPSS version 25.0. Quantitative variables were presented as mean ± standard deviation, while categorical variables were expressed as frequency (%). Post-stratification Chi-square testing was performed, and p≤0.050 was considered statistically significant. Results: The mean age was 9.36 ± 2.949 years. Mean BMI was 22.30 ± 2.34 kg/m2. Gender distribution showed that there was female predominance, i.e., 63 (57.8%) were females. Mean duration of disease was 2.39 ± 1.162 years. Out of 109 patients, 11 (10.1%) developed secondary hemorrhage. The data were stratified according to age, gender, BMI, and duration of disease, and results showed that there was no difference between stratification groups in terms of frequency of secondary hemorrhage (p value>0.050). Conclusions: Secondary hemorrhage after bilateral tonsillectomy by Dissection and Ligation is 10.1% by using silk 2.0 suture for hemostasis. The larger studies with the addition of control groups would provide deep insight into the true significance.